Sport-specific biomechanical responses to an ACL injury prevention programme: A randomised controlled trial - Taylor, J. B.; Ford, K. R.; Schmitz, R. J.; Ross, S. E.; Ackerman, T. A.; Shultz, S. J. (Journal of Sports Sciences, 2018)
Anterior cruciate ligament (ACL) injury prevention programmes have not been as successful at reducing injury rates in women`s basketball as in soccer. This randomised controlled trial (ClinicalTrials.gov #NCT02530333) compared biomechanical adaptations in basketball and soccer players during jump-landing activities after an ACL injury prevention programme. Eighty-seven athletes were cluster randomised into intervention (6-week programme) and control groups. Three-dimensional biomechanical analyses of drop vertical jump (DVJ), double- (SAG-DL) and single-leg (SAG-SL) sagittal, and double- (FRONT-DL) and single-leg (FRONT-SL) frontal plane jump landing tasks were tested before and after the intervention. Peak angles, excursions, and joint moments were analysed using two-way MANCOVAs of post-test scores while controlling for pre-test scores. During SAG-SL the basketball intervention group exhibited increased peak knee abduction angles (p = .004) and excursions (p = .003) compared to the basketball control group (p = .01) and soccer intervention group (p = .01). During FRONT-SL, the basketball intervention group exhibited greater knee flexion excursion after training than the control group (p = .01), but not the soccer intervention group (p = .11). Although women`s soccer players exhibit greater improvements in knee abduction kinematics than basketball players, these athletes largely exhibit similar biomechanical adaptations to ACL injury prevention programmes.